Quality Improvement Of Early Childhood Education Through The Utilization Of Multimedia - Sudarsana, I Ketut (LPM IHDN Denpasar, 2018)
This paper aimed to describe the improvement of the quality of early childhood learning by utilizing various multimedia. The method used was a literature study by exploring various thoughts in various sources that have focused on conducting studies on early childhood education and various multimedia developed. Improving the quality of early childhood learning is very important to be performed in an effort to educate children as early as possible, so that children grow and develop as intelligent individuals, both intellectually, emotionally and spiritually. Teachers and parents need to understand and use various multimedia and guide children so that various aspects of development such as phases and tasks of child development can take place optimally.